Histological and morphometric changes in untraumatised rabbit skeletal muscle treated with deep transverse friction - M. N. Deane; M. A. Gregory; M. Mars (AOSIS, 2002)
Deep transverse friction (DTF) is used in clinical practice and by its nature it may cause muscle injury. This study investigates the morphologic and morphometric changes in untraumatised rabbit skeletal muscle treated with DTF. Method: 16 New Zealand white rabbits were studied. The right vastus lateralis muscle was used as a control and the left vastus lateralis was treated with DTF. Muscle biopsies were taken 10 min, 24 h and 48 h after 1 treatment, 48 h after 2 treatments and 48 h and 6 days after 3 treatments.  Treatments were 48 h apart. Biopsies were prepared for light microscopy and tissue morphometry. Results: After 1 DTF treatment, intracellular and extracellular oedema was noted. Contraction bands seen throughout the fibres suggested severe mechanical trauma to the muscle. 48 hours after 1, 2, and 3 treatments, the muscle appeared to be recovering with reduced oedema, and the contraction banding was limited to small focal areas throughout each fibre. Six days after the last treatment, the myofibers, although normal in diameter, showed small focal areas of super contraction and large internalised inclusion bodies composed of a pool of myofilaments or whorls of membranous material. Morphometry showed oedema to be maximal immediately after treatment. Conclusion: DTF causes a severe but reversible injury to untraumatized myofibers. Its possible mode of action in treatment of injured muscle requires further investigation.